REPRESENTASI FIGUR TERSEMBUNYI DALAM PEMILU 2024: ANALISIS SEMIOTIKA DESAIN SAMPUL MAJALAH TEMPO EDISI “MALU-MAU MENUNDA PEMILU”: REPRESENTATION OF HIDDEN FIGURES IN THE 2024 INDONESIAN ELECTION: SEMIOTIC ANALYSIS OF TEMPO MAGAZINE COVERS “MALU-MAU MENUNDA PEMILU” EDITION - Galih Wisudha Pratama; Drajatno Widi Utomo; Acep Iwan Saidi (Universitas Trisakti, 2024)
Representation of Hidden Figures in The 2024 Indonesian Ellection: Semiotic Analysis of Tempo Magazine Cover “Malu-Mau Menunda Pemilu” Edition. Tempo Magazine regularly publishes issues about the 2024 Election in Indonesia. One of them was published in the edition